‘Ungazilanda in so many ways’ – Theory-making in African languages - Tyler, Robyn; Masola, Athambile; Mpuma, Nondwe (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
Background: In this interview, conducted over Zoom on 13 February 2023, Robyn Tyler (RT) is in conversation with Athambile Masola (AM) and Nondwe Mpuma (NM). Both Athambile and Nondwe are published South African poets as well as full time academics. Athambile published ‘Ilifa’ in 2021 and Nondwe published ‘Peach Country’ in 2022. The transcript of the interview, which has been edited by all three authors, follows, interspersed with reflections by Robyn on the content (in italics).